2022
DOI: 10.1039/d2sc01821g
|View full text |Cite
|
Sign up to set email alerts
|

Silicon functionalization expands the repertoire of Si-rhodamine fluorescent probes

Abstract: Fluorescent dyes such as rhodamines are widely used to assay the activity and image the location of otherwise invisible molecules. Si-rhodamines, in which the bridging oxygen of rhodamines is replaced...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…By now, no SiR dyes (or precursors suitable for SiR synthesis) with alkoxy substituents or with a tert -butyl-substituent have been published, and most of the published SiR dyes show a symmetrical (mainly dimethyl) substitution pattern. Recently, Miller et al achieved the synthesis of a library of Si-bridge-modified SiRs with, in part, two different substituents such as aromatics, alkyl chains, and linkers suitable for ligation (e.g., HaloTag, halogen propyl, azidopropyl, NHS ester) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…By now, no SiR dyes (or precursors suitable for SiR synthesis) with alkoxy substituents or with a tert -butyl-substituent have been published, and most of the published SiR dyes show a symmetrical (mainly dimethyl) substitution pattern. Recently, Miller et al achieved the synthesis of a library of Si-bridge-modified SiRs with, in part, two different substituents such as aromatics, alkyl chains, and linkers suitable for ligation (e.g., HaloTag, halogen propyl, azidopropyl, NHS ester) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it was recently shown that replacement of the methyl groups on the central Si atom of SiR could result in a small red-shift and increase in brightness while providing an alternative position to append functional groups including the HaloTag ligand. [36] Simple structural modifications can also improve fluorophore photostability, a key requirement for extended and quantitative imaging. Although the photobleaching mechanisms of rhodamines are complex and not fully understood, [37] several dye ligands with improved photostability have been reported.…”
Section: Rhodamine-based Ligandsmentioning
confidence: 99%
“…Alkylation at other positions on rhodamines has been scarcely reported. However, it was recently shown that replacement of the methyl groups on the central Si atom of SiR could result in a small red‐shift and increase in brightness while providing an alternative position to append functional groups including the HaloTag ligand [36] . Simple structural modifications can also improve fluorophore photostability, a key requirement for extended and quantitative imaging.…”
Section: Fluorescent and Fluorogenic Ligands For Halotag Protein Labe...mentioning
confidence: 99%
“…Rationally designed 'Si' substituted rhodamines, popularly known as Si-rhodamines have become popular nowadays for bioimaging studies including realtime in vivo imaging, as they possess much longer excitation wavelength (NIR) which can offer the potential for enhanced optical tissue-penetration apart from enabling increased signal to noise ratios (SNRs) and minimized photo-damage. 72,73 In recent times, rhodamine dyes are effectively conjugated with biomolecules and other tags to ensure precise intracellular targeting ability. Apart from possessing excellent photophysical properties, rhodamine dyes can endure spontaneous switching between spirocyclic/open-ring structures which has been exploited recently to perform many super-resolution imaging experiments (discussed in details later).…”
Section: Xanthene/rhodaminementioning
confidence: 99%